Ta có: \(\left|5\left(2x+3\right)\right|+\left|2\left(2x+3\right)\right|+\left|2x+ 3\right|=16\)
\(\Rightarrow5\left|2x+3\right|+2\left|2x+3\right|+\left|2x+3\right|=16\)
\(\Rightarrow\left|2x+3\right|\left(5+2+1\right)=16\)
\(\Rightarrow\left|2x+3\right|.8=16\)
\(\Rightarrow\left|2x+3\right|=2\)
\(\Rightarrow\left[{}\begin{matrix}2x+3=2\\2x+3=-2\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=-1\\2x=-5\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{-1}{2}\\x=\dfrac{-5}{2}\end{matrix}\right.\)
Vậy \(\left[{}\begin{matrix}x=\dfrac{-1}{2}\\x=\dfrac{-5}{2}\end{matrix}\right.\).